Effects of wearing knee-guards on skin pressure and skin blood flow during dynamic motions - Yoon Jeong Baek; Heeyoung Ju; Joo-Young Lee; Kyung Wha Oh (Fashion and Textiles, 2022)
Abstract The purpose of the present study was to explore the effects of wearing knee guards on skin blood flow and skin pressure during dynamic soccer motions. Twenty-one male subjects participated in the following two experimental conditions: wearing knee guards (KG) and no knee guards (Control). Subjects performed several consecutive soccer motions along with a standing position between each motion. Skin blood flow and skin pressure on the thigh, knee, and calf were monitored. The results showed that skin pressure had the greatest value in a sitting position for both the KG condition and Control, but the smallest during instep kicking and switching directions (P < 0.001). The rear calf had the greatest skin pressure for the KG condition (P < 0.001), while the side knee showed the greatest for the Control (P < 0.001). Normalized skin blood flow based on values from their standing position was the greatest during the jump motion among the various soccer motions. Interestingly, skin blood flow decreased by wearing the knee guards on the front thigh and calf (r = − 0.859; r = − 0.835; P < 0.001), while the blood flow increased on the side knee (r = 0.295, P < 0.001). Subjects felt greater skin pressure sensation during the jump motion and switching directions than other soccer positions/motions (P < 0.001). These results indicate that the knee guards result in relatively lighter pressure for dynamic motions (e.g., kick, switching directions, or jump) than for static positions (e.g., sitting or standing), and the skin blood flows for the thigh, knee, and calf are redistributed by wearing the knee guards, especially during jumping.